Effectiveness of Group Recreational Activities of Coloring and Snakes and Ladders on Anxietyand Stress of the Elderly in the Maebashi Elderly Home Maebashi City Gunma Japan - Ajeng Puspita Nugraheni; Byba Melda Suhita; Agustin Widyowati (STRADA : Jurnal Ilmiah Kesehatan, 2026)
An elderly person is someone who has reached the age of 60 years and above. This group has entered the final stages of their life and is vulnerable to various complex problems such as health disorders due to the aging process. This process can cause various problems such as physical, biological, social, economic, and mental problems. Anxiety and stress are mental disorders often experienced by the elderly. Many efforts can be made to reduce anxiety and stress, one of which is recreational group play activities such as coloring and snakes and ladders.